STUDI PERBANDINGAN RELIGIUSITAS SISWA KELAS XI YANG AKTIF DAN TIDAK AKTIF DALAM KEGIATAN EKSTRAKURIKULER (ROHIS) DI SMA NEGERI 2 RAMBAH HILIR KABUPATEN ROKAN HULU - Purwati, Ida Purwati Ida; ', Hambali; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research conducted because of this study religious behavior religiosity student or students at SMAN 2 Rambah Hilir virtually indistinguishable between students who are active and nonactive Rohis. So writer take the title